Human Chorionic Gonadotrophin as a Possible Mediator of Leiomyoma Growth during Pregnancy: Molecular Mechanisms - Sarais, Veronica (Int J Mol Sci, 2017)
Uterine fibroids are the most common gynecologic benign tumors. Studies supporting a strong pregnancy-related growth of leiomyomas generally claimed a crucial role of sex steroid hormones. However, sex steroids are unlikely the unique actors involved as estrogen and progesterone achieve a pick serum concentration in the last trimester while leiomyomas show a typical increase during the first trimester. Given the rapid exponential raise in serum human Chorionic Gonadotrophin (hCG) at the beginning of gestation, we conducted a review to assess the potential role of hCG in the striking growth of leiomyomas during initial pregnancy. Fibroid growth during initial pregnancy seems to correlate to the similar increase of serum hCG levels until 12 weeks of gestation. The presence of functional Luteinizing Hormone/human Chorionic Gonadotropin (LH/hCG) receptors was demonstrated on leiomyomas. In vitro treatment of leiomyoma cells with hCG determines an up to 500% increase in cell number after three days. Expression of cyclin E and cyclin-dependent kinase 1 was significantly increased in leiomyoma cells by hCG treatment. Moreover, upon binding to the receptor, hCG stimulates prolactin secretion in leiomyoma cells, promoting cell proliferation via the mitogen-activated protein kinase cascade. Fibroid enlargement during initial pregnancy may be regulated by serum hCG.